THE KNOWLEDGE OF PREGNANT WOMEN ABOUT PRE-ECLAMPSIA AT THE TAROGONG PUBLIC HEALTH CENTER, GARUT REGENCY - Rizky Ayu Gardelia; Tetti Solehati; Lilis Mamuroh (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
The Maternal Mortality Rate (MMR) in Indonesia is still high, one of the causes is pre-eclampsia. Tarogong Garut is a health center with a high occurrence of preeclampsia and it increases annually, 34% in 2016 increased to 51% in 2017. The knowledge of pregnant women about preeclampsia may be one of the causes to the increased risk of preeclampsia, but there is still limited information available on the knowledge of pregnant women about preeclampsia. This study aimed to discover the knowledge of pregnant women about pre-eclampsia. This type of research was descriptive quantitative with a sample of 83 pregnant women. The sample was selected by the total sample technique. Data analysis used was univariate analysis. The study was conducted at the Tarogong Health Centre in March-July 2018. The instruments used were questionnaires. The results of the study showed that the knowledge of pregnant women about pre-eclampsia is still lacking in all aspects of preeclampsia knowledge, especially in aspects of signs and symptoms. In conclusion, the knowledge of pregnant women about preeclampsia is still lacking. Effective health education programs and methods are needed about preeclampsia for pregnant women, especially in Tarogong Garut.Keywords: Knowledge, Pregnant women, Pre-eclampsia.